ALS702 : Research seminar / Academy of Language Studies - UiTM, Academy of Language Studies (Universiti Teknologi MARA (UiTM), 2021)
This course is designed to enable students to understand the nature, scope and processes of research including research significance and research methodologies. This course also focuses on the analytical and synthesis skills required to review scholarly literature and write a systematic, critical literature review. At the end of the course, students will demonstrate their knowledge and skills by structuring, presenting and writing a research proposal following the conventions for academic writing.